Bedaquiline as a potential agent in the treatment of M. intracellulare and M. avium infections. Issue 3 (23rd March 2017) - Vesenbeckh, Silvan; Schönfeld, Nicolas; Krieger, David; Bettermann, Gudrun; Bauer, Torsten Thomas; Rüssmann, Holger; Mauch, Harald
Recently in this journal, Salfinger and Migliori [1] discussed the accessibility of bedaquiline drug susceptibility testing and the analysis of minimum inhibitory concentrations (MICs) for strains of Mycobacterium tuberculosis . As the recommended treatments for diseases caused by M. avium, and especially M. intracellulare, have high failure rates [2, 3], we measured the MIC of bedaquiline in 20 clinical isolates of these species. Bedaquiline is a potential agent to treat severe or relapsing M. avium-intracellulare complex infections http://ow.ly/n1eR308pERh